Penggunaan Metode Gasing Dalam Meningkatkan Hasil Belajar Matematika Operasi Hitung Perkalian Pada Murid Kelas III SDN Inpres 6/84 Walehunian Sagerat - Damopolii, Janet Kezia; Rorimpandey, Widdy; Ester, Kartini (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to improve the learning outcomes of class III students at SDN Inpres 6/84 Walehunian Sagerat in learning mathematics for multiplication counting operations using the GASING method. The method used is a method that is easy, fun and enjoyable for students. This research uses the Classroom Action Research (PTK) method which consists of four stages, namely the planning stage, action implementation, observation and reflection. The subjects of this research were class III students, totaling 20 students, including 9 men and 11 women. The results of this research show that in the first cycle 16 students completed (79%) while 4 students (21%) did not complete. In cycle II it reached 93%. Based on the results of the research conducted, it can be concluded that the use of the GASING Method in improving mathematics learning outcomes for multiplication arithmetic operations can improve the learning outcomes of class III students at SDN Inpres 6/84 Walehunian Sagerat.